An Inclusive Pedagogical Framework for Teaching English Vocabulary to Learners with Disabilities in the Indonesian Context - Mesrawati Mesrawati (CV. Arunika Media Nusantara, 2025)
This study aims to find out (1) the vocabulary teaching strategy used by teachers for students with mixed hearing impairment and (2) how to implement the strategy for teaching English vocabulary to students with mixed hearing impairment. This study applied a qualitative method. The participants of this research were one English teacher and five students of eighth-grade SLB Negeri Wonomulyo in the category of hearing impairment, which was taken through a purposive sampling technique. The data of this study were collected by observation, interview, and documentation. The obtained data were analyzed in four major phases: data collection, display, condensation, and conclusion drawing. The result of this study revealed that (1) there were four strategies used by an English teacher in teaching English vocabulary to disabled students, namely sign language, gesture, writing language, and tadoma. (2) the teacher implemented the strategies by combining all of them. The teacher showed students the material, such as explanations and vocabulary, by writing it on the whiteboard. Next, the teacher explained it to the students using sign language and gestures; when they could not read lip language, the teacher taught using the tadoma strategy.